Naltrexone Initiation in the Inpatient Setting for Alcohol Use Disorder: A Systematic Review of Clinical Outcomes - Kirchoff, Robert W. (Mayo Clin Proc Innov Qual Outcomes, 2021)
Alcohol use disorder (AUD) is a highly prevalent health issue in the United States. The number of those receiving medication-assisted treatment (MAT) is limited, despite strong evidence for their effectiveness. The inpatient setting may represent an important opportunity to initiate MAT. The goal of this study was to summarize the data on naltrexone initiation in the emergency department or inpatient setting for the management of AUDs. We searched ClinicalTrials.gov, Ovid EBM Reviews, Ovid Embase, Ovid Medline, Ovid PsycINFO, Scopus, and Web of Science from inception through October 31, 2019. Search strategies were created using a combination of keywords (Supplemental Appendix 1, available online at http://www.mcpiqojournal.org) and standardized index terms related to naltrexone therapy for medically hospitalized patients with AUD. Two uncontrolled pre-post study designs evaluated naltrexone prescription rates, 30-day readmission rates, and rehospitalization rates. Two authors independently abstracted data on study characteristics, results, and study-level risk of bias. The research team collaborated to assess the strength of evidence across studies. Two studies reported that implementing a protocol for naltrexone initiation increased MAT rates, with one study noting a substantial decrease in 30-day hospital readmissions. Overall, we found that there is a paucity of data on naltrexone initiation in the inpatient setting for AUDs. This likely reflects the nature of current clinical practice and prescriber comfortability. There is a need for further studies evaluating MAT initiation in the inpatient setting. Furthermore, efforts to increase provider knowledge of these therapeutic options are in need of further exploration.